Note a margine di una celebre ‘lampa’ leopardiana - Petrucci, Chiara (Rivista Internazionale di Studi Leopardiani, 2022)
The discovery of a new source for a verse of La sera del dì di festa gives an opportunity to browse the relationship between Giacomo Leopardi and the works of the XVII century classicistic poet Gabriello Chiabrera.